ANALISIS MEKANISME CORPORATE GOVERNANCE PADA PEMBERIAN OPINI AUDIT DENGAN PENJELASAN GOING CONCERN - Arum Ardianingsih (Jurnal Ekonomi Dan Bisnis, 2015)
This research aim to know influence from corporate governance mechanism to audit opinion withgoing concern explanatory. The population research was the listed companies running inProcessing/Manufacturing Sector. Sampling method was conducted with Purposive Sampling technique,produced 157 sample units. The observation period of this study was from 2004 to 2006. The dependentvariable is a dummy variable representing the presence of Audit report with going concern explanation.Independent variables consist of Board of commissioner changes, board of director changes, auditcommittee and auditor quality as proxy from corporate governance mechanism. The hypotheses proposedwere tested by logistic regression. The hypotheses proposed were tested by logistic regression show that board of director changes,auditor quality is significant, while board of commissioner changes and audit committee is not significant tothe audit opinion with going concern explanatory.   Keywords: Audit Opinion, Audit Opinion with Going Concern Explanatory, Corporate Governance Mechanism.